(3CNHGQ eUQs - (3CHh YeQh eMeO Hf jhSa Hf jYbhH, GdcfOj GdeUQj,J (B350 (3g` s
(3ChdgG (B:s
(3CNHQ CHh YeQ YHOGdQMef Hf YeQ Hf eMeO GdYOd bGd CNHQfG CHhYeQh jhSa Hf jYbhH GdcfOi GdeUQi gfG cJGH CeQ jLeYg CHhGdeSc cGahQ JPcQ ajg eUQ heGNUgG Gddg Hg ef GdaVd hGdHQcGJ s
(3BNQgG (B:s
(3bGd CHG GdMSf CeG jSeY jG QShd Gddg hGddg hQShdg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B149 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B10 s
(3eUOQ GbJfGA GdCUd (B:s
(3eJMa GdCKGQ GdadSWjfi HGdbOS , eUhQg Yf fSNI HLGeY CMeO HGTG GdLRGQ s
Keywords: (3GdJGQjNs